Piezoelectric energy harvesting - Erturk, Alper; Inman, D. J. (Chichester : Wiley, 2011)
'The goal is to eliminate the need for periodic battery replacement or external power sources in situations where this would otherwise be difficult or impossible to provide, such as remote wireless sensors used in hazardous environments or for structural health monitoring applications'--
Includes bibliographical references and index.
Keywords: Piezoelectric transducers; Electric generators; Piezoelectricity; Energy harvesting